Biomechanics and improving athletic performance in the 100m race - sbaa, bouabdlah; Torki, ahmed; Mouissi, Farid (sports creativity, 2025)
My contribution falls within the realm of improving athletic performance, and this topic is addressed to all athletes, at all levels. We can elevate athletic performance and bring it to its full potential (improving performance, facilitating its measurement, and establishing a suitable relationship between performance and set goals). Therefore, improving performance requires us to consider a range of contexts, the athlete's specific characteristics, and the objectives set. Improving training relies on highly complex procedures that involve employing precise knowledge of a range of factors controlling athletic performance, starting from the athlete's individual characteristics. It also involves incorporating the athlete's knowledge into the application of measurement procedures, as well as drawing upon physiological, psychological, sociological, and biomechanical knowledge. All of this knowledge is responsible for planning physical exertion. The process of improving performance requires multiple competencies and knowledge in various fields, often concentrated in the coach's personality, with some of it possessed by the athlete. Understanding the details of athletic performance is of paramount importance, especially in events where fractions of a second determine the outcome. This is where the crucial role of identifying the biomechanical variables and indicators responsible for achieving victory in sprint races becomes apparent. Many, if not most, sports clubs overlook the importance of biomechanics in improving athletic performance. Biomechanics applies physical laws and mechanical systems to the human body, representing the cognitive mechanisms responsible for movement trajectory and organization, as well as the determinants of movement and the action and reaction forces that govern it. Due to the scarcity of experts in this field and the lack of modern technological tools for gathering movement data, many coaches consider it a complex science far removed from practical application in sports. It is rare to find a coach or sports club seeking the expertise of a biomechanics specialist in sports to enhance athletic performance and provide technical and quantitative information. In fact, attention to this field has become a significant differentiator between athletes, even when their abilities are similar in other performance determinants.